Food safety culture and risk factors: a case study in Melaka tourist spots/ Ungku Fatimah Ungku Zainal Abidin ... [et al.] - Ungku Zainal Abidin, Ungku Fatimah; Roslan, Aifaa; Mustafar, Siti Sarah; Che Ishak, Farah Adibah; Abdul Karim, Muhamad Shahrim (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The purpose of this study is to examine the elements of food safety culture in micro and small restaurants located in tourist spots and to assess risk factors of food handler noncompliance. The study employed a qualitative approach, collecting data through observation and interviews with restaurant managers and food handlers. A total of 20 informants from 10 restaurants participated in interview sessions. Altogether ten themes emerged based on elements of food safety culture within micro and small restaurants: 1) leadership and management support, 2) communication, 3) management system, style, and process, 4) accountability, 5) internal environmental factors, 6) risk perception and risk awareness, 7) teamwork, 8) work pressure 9) customer perception, and 10) home culture. In this study, two new themes emerged in comparison to previous works: 1) customer perception and 2) home culture. The findings indicate that food safety culture in micro and small restaurants is formed primarily through interpersonal skills rather than job-specific knowledge and skills. Interpersonal attributes and the ability to work with others are required, which include communication, leadership, self-commitment, and teamwork. The observation results showed that the two most commonly occurring risk factors out of compliance in the studied restaurants were poor personal hygiene and improper holding time and temperature. The findings provide insights into the food safety culture of this under-studied context to help better planning on training strategies and development of interventions to improve food safety practices.